Pengaruh Personality Traits dan Competitive Advantage terhadap Keberlanjutan Usaha Dimoderasi Oleh Social Innovation Orientation - Ajeng Wijayanti; Dian Fitri Hanandia (Politeknik Ganesha Medan, 2022)
This study aims to prove the moderation of social innovation orientation on the influence of personality traits and competitive advantage on business sustainability. The sample used is 100 business owners based in Jakarta. The research method used in this study is structural equation modeling by proving several research hypotheses using the Smart PLS software. This study proves that personality traits have no significant effect on business sustainability, while competitive advantage independently can affect business sustainability. For interaction moderation, social innovation orientation concluded that the results weakened personality traits towards business sustainability and for moderation interaction, social innovation orientation concluded that it was not moderating and weakened competitive advantage on business sustainability. A company must have a competitive advantage in order to compete more effectively in the business world. Strategies need to be developed properly to work with others in order to create company sustainability. Social innovation affects the sustainable development of enterprises and achieves social needs without harming the natural environment. Social innovation orientation can clearly play an important role in solving social problems with novel and innovative ideas that contribute to social value outcomes. However, every company requires extra effort and a well-planned strategy if it wants to maximize the sustainability of its company going forward.